2006
DOI: 10.1037/1089-2699.10.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of task instructions and brief breaks on brainstorming.

Abstract: Experiment 1 examined the effects of additional brainstorming rules for groups and looked at whether the presence of a facilitator who actively enforced the rules of brainstorming was beneficial. Experiments 2 and 3 examined whether the additional rules and brief breaks were beneficial to individual brainwriters and electronic brainstormers working alone. Clear benefits of the additional rules were found under a variety of conditions. The presence of a facilitator to enforce the rules enhanced the efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 34 publications
1
84
0
1
Order By: Relevance
“…Studies in the area of brainstorming have revealed that the task decomposition leads to increased ideation in groups (Coskun, Paulus, Brown & Sherwood, 2000;Paulus, Nakui & Putman, 2006). However, the task decomposition in brainstorming research did not involve assignment of subtasks to individual members.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the area of brainstorming have revealed that the task decomposition leads to increased ideation in groups (Coskun, Paulus, Brown & Sherwood, 2000;Paulus, Nakui & Putman, 2006). However, the task decomposition in brainstorming research did not involve assignment of subtasks to individual members.…”
Section: Introductionmentioning
confidence: 99%
“…However, some researchers argue that group idea generation could be less effective than individual (Mullen et al, 1991). Many studies had been carried out to explain for the productivity loss in this type of group work and to search for solutions (Diehl & Stroebe, 1987;Mullen et al, 1991;Brown & Paulus, 1996;Brown & Putman, 2006;Putman & Paulus, 2009). Especially, there was a module to train people to generate more ideas and higher quality of ideas in problem…”
Section: Rationalementioning
confidence: 99%
“…In all these experiments, social comparison was created by means of direct and explicit information (a group performance standard, individual performance levels) in the absence of implicit contextual information (group awareness, situation awareness, or performance perception). Indeed in these experiments, the participants' challengers were always physically absent (Paulus & Dzindolet, 1993;Shepherd et al, 1995;Dugosh & Paulus, 2005;Michinov & Primois, 2005) or they were present but worked on separate computers and had no clue to the others' performance level (Paulus et al, 2006). In other words, these experiments simulated social comparison in order to better control it.…”
Section: 2mentioning
confidence: 99%
“…The benefits of social comparison are well-known. They can be observed for example when individual outputs are identifiable (with comparison to a situation where outputs are pooled, see Harkins & Jackson, 1985), when participants believe that their output will be evaluated (Bartis et al, 1988), when they are given a performance standard for their task (Paulus & Dzindolet, 1993;Shepherd et al, 1995), when they are exposed to the ideas of other participants (with comparison to a situation where they think the ideas come from a computer, see Dugosh & Paulus, 2005), or when they are periodically informed of each one's performance level (Michinov & Primois, 2005;Paulus et al, 2006). In all these experiments, social comparison was created by means of direct and explicit information (a group performance standard, individual performance levels) in the absence of implicit contextual information (group awareness, situation awareness, or performance perception).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation